ISSUES OF QUALIFICATION OF THE CRIME OF MURDER OR THREATENING OF VIOLENCE AND DIFFERENTIATION FROM SIMILAR CRIMES - Djumaevich, Khaydarov Shukhratjon (Journal of Contemporary Business Law & Technology: Cyber Law, Blockchain, and Legal Innovations, 2024)
This article explores the complexities surrounding the crime of killing or intimidation involving violence, aiming to differentiate it from analogous offenses. General Background: The prevalence of violent crimes necessitates a nuanced understanding of their classifications within legal frameworks. Specific Background: Scholars have expressed divergent views on the qualification of homicide and intimidation, prompting a closer examination of existing literature and legal definitions. Knowledge Gap: Despite significant discourse, there remains a lack of consensus regarding the parameters that distinguish these crimes from related violent acts, particularly in terms of preparation, execution, and attempted offenses. Aims: This study seeks to clarify the distinctions between murder, intimidation, and other violent crimes, offering a comprehensive scientific analysis of their characteristics and legal implications. Results: Through critical analysis of theoretical perspectives and legal interpretations, the findings reveal specific elements that delineate homicide and intimidation from other violent actions, particularly in terms of intent and methodology. Novelty: The article introduces a refined classification framework, integrating insights from criminology and legal studies to address the identified knowledge gap. Implications: The conclusions drawn from this analysis not only enhance the understanding of violent crime classification but also provide practical implications for legal practitioners and policymakers, fostering improved strategies for crime prevention and prosecution. This contribution underscores the importance of precise legal terminology in effectively addressing and mitigating violence in society.